Dietary Interventions to Treat Type 2 Diabetes in Adults with a Goal of Remission: An Expert Consensus Statement from the American College of Lifestyle Medicine. Issue 3 (May 2022) - Rosenfeld, Richard M.; Kelly, John H.; Agarwal, Monica; Aspry, Karen; Barnett, Ted; Davis, Brenda C.; Fields, Denise; Gaillard, Trudy; Gulati, Mahima; Guthrie, George E.; Moore, Denee J.; Panigrahi, Gunadhar; et al.
Objective: The objective of this Expert Consensus Statement is to assist clinicians in achieving remission of type 2 diabetes (T2D) in adults using diet as a primary intervention. Evidence-informed statements agreed upon by a multi-disciplinary panel of expert healthcare professionals were used. Methods: Panel members with expertise in diabetes treatment, research, and remission followed an established methodology for developing consensus statements using a modified Delphi process. A search strategist systematically reviewed the literature, and the best available evidence was used to compose statements regarding dietary interventions in adults 18 years and older diagnosed with T2D. Topics with significant practice variation and those that would result in remission of T2D were prioritized. Using an iterative, online process, panel members expressed levels of agreement with the statements, resulting in classification as consensus, near-consensus, or non-consensus based on mean responses and the number of outliers. Results: The expert panel identified 131 candidate consensus statements that focused on addressing the following high-yield topics: (1) definitions and basic concepts; (2) diet and remission of T2D; (3) dietary specifics and types of diets; (4) adjuvant and alternative interventions; (5) support, monitoring, and adherence to therapy; (6) weight loss; and (7) payment and policy. After 4 iterations of the Delphi survey and removal of duplicative statements, 69 statements met the criteria for consensus, 5 were designated as near consensus, and 60 were designated as no consensus. In addition, the consensus was reached on the following key issues: (a) Remission of T2D should be defined as HbA1c <6.5% for at least 3 months with no surgery, devices, or active pharmacologic therapy for the specific purpose of lowering blood glucose; (b) diet as a primary intervention for T2D can achieve remission in many adults with T2D and is related to the intensity of the intervention; and (c) diet as a primary intervention for T2D is most effective in achieving remission when emphasizing whole, plant-based foods with minimal consumption of meat and other animal products. Many additional statements that achieved consensus are highlighted in a tabular presentation in the manuscript and elaborated upon in the discussion section. Conclusion: Expert consensus was achieved for 69 statements pertaining to diet and remission of T2D, dietary specifics and types of diets, adjuvant and alternative interventions, support, monitoring, adherence to therapy, weight loss, and payment and policy. Clinicians can use these statements to improve quality of care, inform policy and protocols, and identify areas of uncertainty.